PRODUCTIVITY AND YIELD OF SEED TUBERS WHEN CULTIVATING EARLY POTATO VARIETIES WITH TUBERS AND SPROUTS IN THE CONDITIONS OF THE KASHKADARYA REGION (Proceedings of International Educators Conference, 2024)
The article presents the results of evaluating the early potato varieties Gala, Arizona, Sylvana, Saviola, Evolution, Sifra, Bogizogon, Ultraeshim and Yangi O’zbekiston-Sayqal for the yield of seedlings and their survival rate when cultivating seed tubers of different sizes (30-50, 50-70 and 80-100 g). In addition, data are provided on field germination (survival), growth, top formation, duration of the growing season and yield when planting seed tubers and sprouts planted in each nest in 1, 2 and 3 pieces, as well as tubers without sprouts, treated in a 4% solution of ammophos and growth stimulants.